Studies on the Antiviral and Cytotoxic Activity of Schiff Bases Derived from 1,2-Bis-(o- and p-aminophenoxy)ethane and Salicylaldehyde - Bulut, Hakan; Karatepe, Mustafa; Temel, Hamdi; Sekerci, Memet; Koparir, Metin (Asian Journal of Chemistry, 2016)
A new synthesized derivative of substituted salicylaldehyde Schiff bases of aminophenoxy ethane were selected as new biological agents in the present study. The results indicate that none of the tested compounds was found to be an antiviral agent for DNA (bovine herpesvirus 1; BHV-1) and RNA (parainfluenza-3 viruses; PI-3) viruses used in this study but they possess highly cytotoxic effects.